Long-term outcomes of pre-emptive valganciclovir compared with valacyclovir prophylaxis for prevention of cytomegalovirus in renal transplantation - Reischig, Tomas; Hribova, Petra; Jindra, Pavel; Hes, Ondrej; Bouda, Mirko; Treska, Vladislav; Viklicky, Ondrej (Journal of the American Society of Nephrology, 2012)
Prevention of cytomegalovirus (CMV) is essential in organ transplantation. The two main strategies are pre-emptive therapy, in which one screens for and treats asymptomatic CMV viremia, and universal antiviral prophylaxis. We compared these strategies and examined long-term outcomes in a randomized, open-label, single-center trial. We randomly assigned 70 renal transplant recipients (CMV-seropositive recipient or donor) to 3-month prophylaxis with valacyclovir (n=34) or pre-emptive valganciclovir for significant CMV viremia detected at predefined assessments through month 12 (n=36). Among the 55 patients who had a protocol biopsy specimen available at 3 years to allow assessment of the primary outcome, 9 (38%) of 24 patients in the prophylaxis group and 6 (19%) of 31 patients in the pre-emptive therapy group had moderate to severe interstitial fibrosis and tubular atrophy (odds ratio, 2.50; 95% confidence interval, 0.74-8.43; P=0.22). The prophylaxis group had significantly higher intrarenal mRNA expression of genes involved in fibrogenesis. The occurrence of CMV disease was similar in both groups, but pre-emptive therapy improved 4-year graft survival (92% versus 74%; P=0.049) as a result of worse outcomes in patients with late-onset CMV viremia. In conclusion, compared with valacyclovir prophylaxis, pre-emptive valganciclovir therapy may lead to less severe interstitial fibrosis and tubular atrophy and to significantly better graft survival.
Keywords: Biopsy; Humans; Longitudinal Studies; Cytomegalovirus; lidé středního věku; Cytomegalovirus Infections; Atrophy; Valacyclovir; valganciklovir; ledviny; fibróza; Female; Fibrosis; Valine; dospělí; cytomegalovirové infekce; přežívání štěpu; Kidney; výsledek terapie; valaciclovir; lidé; valin; biopsie; atrofie; Adult; transplantace ledvin; Follow-Up Studies; ženské pohlaví; Kaplanův-Meierův odhad; longitudinální studie; Male; Ganciclovir; antivirové látky; Acyclovir; Middle Aged; Treatment Outcome; acyklovir; Antiviral Agents; Kidney Transplantation; Valganciclovir; Kaplan-Meier Estimate; mužské pohlaví; Graft Survival; následné studie; ganciklovir